THE ROLE AND PLACE OF THE VICTIM'S REPRESENTATIVE IN THE DETERMINATION OF PROPERTY DAMAGE AND DAMAGES CAUSED BY A CRIMINAL OFFENSE (Bulletin of criminological association of Ukraine, 2024)
The article substantiates that one of the constitutional rights of a person is the right to receive compensation for damage caused to him, including damage caused by a criminal offense. It was determined that in the criminal process, this right has now been embodied in an independent function of criminal proceedings, and the procedural order of its implementation is defined in a separate institution of the criminal process. It is argued that despite the legal regulation of the victim's right to compensation for the damage caused to him, certain aspects of the criminal procedural activity in this direction are still neglected, among them, in particular, the voluntary procedure for compensation for the damage caused, as well as ensuring the rights of the victim in terms of determining the amount of damage caused and ways to ensure its compensation. The above highlighted the need to involve a lawyer to represent these interests of the victim. It was found that the advantages of the participation of a lawyer are primarily the possibility of using the powers guaranteed by professional status in the context of the provisions of the Law of Ukraine «On Advocacy and Advocacy», in the areas of gathering evidence and drafting a civil lawsuit, however, these areas of activity also need to be expanded and improved, therefore several changes to the criminal procedural legislation have been proposed.
Keywords: criminal process; participant in criminal proceedings; damage; victim; lawyer; victim's representative; authority; legal basis